The Pubilsh Journal Hubungan Faktor Predisposing terhadap Perilaku Pencarian Pengobatan TB Baru di Wilayah Kerja Puskesmas Cilongok 1 - Leli Ngatikoh; Madyo Maryoto; Mariah Ulfah (Universitas Harapan Bangsa, 2021)
Abstact Tuberculosis (TB) is an infectious disease that causes the most deaths and it is a dangerous threat to public health. TB is one of the top 10 causes of death in the world. Objective: To identify the influence of predisposing factors on the behavior of seeking treatment for pulmonary7 TB7 in the7 work7 area7 of7 ​​the Cilongok I Public Health Center, Banyumas Regency. Methods: This study used a correlational analysis method with a cross-sectional study design. The sample in this study were patients in the Cilongok I Public Health Center area who suffered pulmonary TB, with 46 participants. The research uses purposive sampling technique where the research instrument was questionnaire. Analysis of the data in this study is to use the Chi Square test calculation using SPSS. Results: Statistically it can be proven that there is no influence between economic status and behavior seeking treatment for pulmonary TB because the p-value is 0.345 (> 0.05), there is relation of knowledge on treatment-seeking behavior with p-value = 0.003, there is relation of the attitude of pulmonary TB patients on seeking behavior. treatment p-value = 0.02, there is no relation of education with treatment seeking behavior for pulmonary TB..